Analisis Pengaruh Celebrity Trust terhadap Konstruk Kredibilitas dan Ekuitas Merek Kosmetik Lokal Indonesia - Rinaldi, Marelita (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The rapid development in the cosmetics industry in Indonesia has triggered competition between companies. The marketing strategy using celebrity endorsements is one of the strategies often used by cosmetic companies. Supported by the Korean wave phenomenon in Indonesia, several local cosmetic industry companies have started using celebrity endorsements with South Korean celebrities. This study aims to determine the effect of celebrity trust on advertising credibility, brand credibility, and brand equity in local cosmetic companies that endorse celebrities with South Korean celebrities. The data in this study were obtained through online questionnaires distributed through social media. Data were obtained from 222 respondents then analysed using the PLS-SEM method. The research analysis results show that celebrity trust is positively and significantly related to advertising and brand credibility. Advertising credibility and brand credibility are positively and significantly related to brand equity.